From Coping Strategies to Fan Well-Being: Resource Dynamics of Team Identification, Impulse Control, and Psychological Capital in Negative Experiences - Hyun-Woo Lee; Yelim Yoo; Kun Chang; Jun-Phil Uhm (Journal of Applied Sports Management, 2025)
Guided by conservation of resources theory, the authors examine how team identification, impulse control difficulties, coping strategies, and psychological capital shape fans’ well-being in negative fan experiences. Survey from 300 sport fans were analyzed using structural equation modeling. Results showed that identification promoted adaptive coping and reduced cutting off reflected failure, whereas impulse control difficulties increased denial and cutting off reflected failure. Denial unexpectedly enhanced psychological capital while reducing well-being, and venting functioned as a double-edged mediator across positive/negative pathways. Psychological capital was the strongest predictor of well-being, underscoring its role as a central resource linking coping to outcomes.
Keywords: team identification; impulse control difficulties; coping strategies; psychological capital; well-being